2020
DOI: 10.1097/wnr.0000000000001518
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture at GV24 and bilateral GB13 improves cognitive ability via influences the levels of Aβ, p-tau (s396) and p-tau (s404) in the hippocampus of Alzheimer’s disease model rats

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
(34 reference statements)
0
10
0
Order By: Relevance
“…Additionally, many serine phosphorylation sites on the Tau protein were found to be phosphorylated in AD mice, including Ser199, Ser202, Ser396, and Ser404 [ 46 48 ]. The mechanism underlying the improvement of cognitive function by EA at GV24 and GB13 may be related to the reduction of Aβ, p-Tau (Ser396), and p-Tau (Ser404) in the hippocampi of AD rats [ 49 ]. Additionally, 2 Hz EA at GV20 and BL23 caused a decrease in hippocampal Aβ and p-Tau (Ser404) [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, many serine phosphorylation sites on the Tau protein were found to be phosphorylated in AD mice, including Ser199, Ser202, Ser396, and Ser404 [ 46 48 ]. The mechanism underlying the improvement of cognitive function by EA at GV24 and GB13 may be related to the reduction of Aβ, p-Tau (Ser396), and p-Tau (Ser404) in the hippocampi of AD rats [ 49 ]. Additionally, 2 Hz EA at GV20 and BL23 caused a decrease in hippocampal Aβ and p-Tau (Ser404) [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…The cells would be cultured and levels of Aβ would be measured in cell culture media [12]. Immunofluorescence labeling would be used to detect the protein expression levels of p-tau following the Yang et al methodology [5]. BDNF in frozen rat cortical tissue lysates would also be measured using BDNF ELISA immunoassays [11].…”
Section: Aβ Peptide P-tau and Bdnf Level Measurementmentioning
confidence: 99%
“…These amyloid plaques and NFTs can form within neurons, essentially destroying cell function in the hippocampal region by decreasing the number of neural cells and synapses. [5]. Not only are Aβ peptides and p-tau believed highly associated with cognitive decline, but they are also said to contribute to pathologic changes such as neuroinflammation, loss of hippocampal volume, brain atrophy and neurovascular dysfunction [3].…”
Section: Introductionmentioning
confidence: 99%
“…Randomized controlled trials (RCTs) suggested that acupuncture could improve cognitive function in patients with mild to moderate cognitive impairment ( 10 , 11 ). In addition, animal experiments are trying to clarify the mechanism of acupuncture ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%